PERTUMBUHAN Tetraselmis Sp DI MEDIA KULTUR BERBEDA DENGAN PENAMBAHAN Pb2+ - Astri Pujiastuti; Moh Muhaemin; Henni Wijayanti (Jurusan Perikanan dan Kelautan, 2012)
Lead has known as toxic metal element in water environment which may come from domestic and industrial waste systems. Recent research proved that microalgae may reduce lead concentration by using bioaccumulation mechanism to the threshold level approximately. Tetraselmis is marine microalgae which has sensitive respond to heavy metal. The research aim was to determined the bioacumulation treshold effect of specific heavy metal (lead) on marine microalgae Tetraselmis sp. The research was conducted on July 2010 in BBPBL Hanura Lampung Province. The research was used two different media (TMRL and Conwy) and each treatment was added lead of 0,25 mg/l. Data was analyzed by using simple linier regression model to found the correlation between microalgae density and present of heavy metal. The result showed that the media has not significant effect on bioaccumulation ability of Tetraselmis sp. In the other hand, the present of heavy metal on media has positive correllation to initial concentration of heavy metal on microalgae biomass (rConwy=0,657; rTMRL=0,682).